Tkáňová koncentrace kalcitoninu jako marker lokální a systémové progrese karcinomu prostaty - Šafařík, Libor; Jarolím, Ladislav; Dušková, Jaroslava; Vachalovský, Vít; Dvořáček, Jan; Víšek, Jan Ámos (Iga MZ ČR, 2000)
Prostatic tissue taken away by the radical prostatectomy should by homogenised and the level of calcitonin /ng/g/ and ploidity would be determined. Preoperativelly and in 6 month terms PSA, calcitonin, scintigraphy of bones should be performed. In the study, there should be included 40 patients operated on prostatic cancer at Dept. of Urology, Prague, PSA and calcitonin would be immunoanalytically assayed at Dept. of Endocrinology, Prague, Cytoflowmetry should be performed at Dept. of Oncology.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: nádorové biomarkery; ploidie; urologie; Biomarkers; Prostate-Specific Antigen; nádory prostaty; kalcitonin; DNA; biologické markery; chemie, klinická chemie; Biomarkers, Tumor; Ploidies; Prostatic Neoplasms; Calcitonin; onkologie; prostatický specifický antigen